QoS Analysis of IMS Signalling in UMTS Networks - Vosylius, V.; Pauliukas, D. (Elektronika ir Elektrotechnika, 2010)
Purpose of the research was to analyze SIP protocols call setup signalization operations in the IP Multimedia Subsystem and to evaluate how it affects quality of service to the UMTS R5 network. For the research we used simplified model of the IMS network and analyzed SIP signalization information flow in IMS nodes. For analysis of signalization traffic we applied queue M/D/1 model. For known total delay of the whole IMS we calculated possible utilization parameter of the whole IMS and its nodes separately when user distribution is also known. Using this method we calculated that S-CSCF node is loaded the most during call setup signalling procedure in IMS.